Gender perspectives on health and medicine key themes - Segal, Marcia Texler, 1940-; Demos, Vasilikie P.; Kronenfeld, Jennie J. (Amsterdam ; Boston : Elsevier/JAI, 2003)
This volume is about gender, health and medicine broadly defined. From the essays in it, it is abundantly clear that medicine is a gendered and class-structured institution. Taken as a whole the volume offers a critique of exclusively biomedical approaches to personal and public health and calls for more sociological input, qualitative research and an intersectional approach to help us understand various aspects of health and illness. Among the recurrent themes in the seven essays are the medicalization of personal and social problems, the commodification of healthcare, and questions of agency, responsibility and control on the parts of recipients and dispensers of healthcare. Six of the seven essays deal with Western medicine exclusively, the seventh examines a situation where women have a choice between Western and traditional treatment. Timely topics such as somatic distress among women with breast cancer, drug company funding of research on women's sexual problems, and racial and ethnic health disparities are represented. A companion volume will focus on conventional and unconventional approaches to managing pregnancy and childbirth. The intended audience is the social science community, especially those who are interested in the social scientific study of medicine or of gender including those who may not be familiar with the areas in which the two overlap.
Gendered perspectives on medicine: an introduction / Marcia Texler Segal, Vasilikie Demos, Jennie Jacobs Kronenfeld -- Situating epidemiology / Beth E. Jackson -- Gendering the medicalization thesis / Elianne Riska -- "Big pharma" in our bedrooms: an analysis of the medicalization of women's sexual problems / Heather Hartley -- The continuum: somatic distress to medicalization in women with breast cancer: theoretical and empirical assessment / Erica S. Breslau -- Intersectionality and women's health: charting a path to eliminating health disparities / Lynn Weber, Deborah Parra-Medina -- "We're not a part of society, we don't have a say": exclusion as a determinant of poor women's health / Colleen Reid -- Rariu and Luo women: illness as resistance to men and medicine in rural Kenya / Nancy Luke.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Women -- Health and hygiene -- Sociological aspects; Social medicine; Health -- Sex differences; Medical care -- Sex differences; Gender Identity; Social Medicine -- methods; Delivery of Health Care -- ethics; Women's Health -- ethics; Women's Rights; Gender studies, gender groups; Personal & public health; Medical -- Health Care Delivery